Solid Carbon Produced in an Inductively Coupled Plasma Torch with a Titan Like Atmosphere - D. Vacher; S. Menecier; M. Dudeck; M. Dubois; B. Devouard; E. Petit (International Journal of Aerospace Engineering)
Solid carbon is deposited on the surfaces of an inductively coupled plasma torch operating with a Titan like atmosphere plasma gas. The frame of the initial research is the study of the radiative properties of plasma encountered around a spacecraft during its hypersonic entry in upper layers of planetary atmosphere. Deposition of carbon is observed not only on the quartz tube outside the inductor but also on the ceramic protection of the torch injector. Carbon exhibits two types of morphology more or less dense and it is analyzed by various analytic devices as MEB, SEM, TEM, EDS and Raman spectroscopy. The gathered carbon powder shows the presence of nanostructured particles.